Radical antegrade modular pancreatosplenectomy for adenocarcinomaof the body of the pancreas in a patient with portal annular pancreas, aberrant hepatic artery, and absence of the celiac trunk: A case report. Issue 48 (December 2017) - Yuan, Hao; Wu, Pengfei; Chen, Jianmin; Lu, Zipeng; Chen, Lei; Wei, Jishu; Guo, Feng; Cai, Baobao; Yin, Jie; Xu, Dong; Jiang, Kuirong; Miao, Yi
Abstract: Rationale: Portal annular pancreas is a rare anatomic variation, where the uncinated process of the pancreas connects with the dorsal pancreas and the pancreas tissue encases the portal vein (PV), superior mesenteric vein (SMV) or splenic vein (SV). Malignancies are quite uncommon in the patients, who have an annular pancreas especially portal annular pancreas. Ectopic common hepatic artery and absence of the celiac trunk (CT) are the other infrequent abnormalities. Patient concerns: A 74-year-old man suffered from upper abdominal and back pain. Diagnoses and Interventions: Contrast enhanced computed tomography indicated a low-density mass in the body of the pancreas. Pathological report showed adenocarcinoma of the body of pancreas after radical antegrade modular pancreatosplenectomy (RAMPS). Outcomes: In the operation, we found the superior vein and portal vein was surrounded by the pancreatic tissue. The left gastric artery and splenic artery originated respectively from abdominal aorta, and celiac trunk was not viewed. In addition, the common hepatic artery was a branch from the superior mesenteric artery. Lessons: In general, this is a novel clinical case of pancreatic carcinoma happening in the portal annular pancreas which was accompanied with aberrant hepatic artery and absence of the celiac trunk at the same time. Confronted with the pancreatic neoplasms, the possibility of coexistent annular pancreas and arterial variations should be considered. Abstract : Supplemental Digital Content is available in the text